2018
DOI: 10.5415/apallergy.2018.8.e29
|View full text |Cite
|
Sign up to set email alerts
|

Cashew nut allergy in Singaporean children

Abstract: BackgroundThere has been an increasing trend of nut allergies in Singapore.ObjectiveThe aim of this study was to review the clinical characteristics of children with cashew nut allergy.MethodsA retrospective analysis was conducted in a tertiary paediatric referral centre in Singapore from 2008 to 2015. A total of 99 subjects with positive specific IgE (≥0.35 IU/L) to cashew nut were identified. Clinical features including demographics, clinical reaction to cashew nut, associations with other nuts and test spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Nevertheless, there are no clinical studies confirming its effective medicinal efficacy [122]. On the other hand, the rapid inclusion of cashews in dietary habits has led to an extended sensitization and allergy to this food all over the world [123][124][125][126]. Published reports reveal that cashew allergy is found to a greater extent in children [123,127] and in adult women [128].…”
Section: Cashew 231 General Information and Main Allergensmentioning
confidence: 99%
“…Nevertheless, there are no clinical studies confirming its effective medicinal efficacy [122]. On the other hand, the rapid inclusion of cashews in dietary habits has led to an extended sensitization and allergy to this food all over the world [123][124][125][126]. Published reports reveal that cashew allergy is found to a greater extent in children [123,127] and in adult women [128].…”
Section: Cashew 231 General Information and Main Allergensmentioning
confidence: 99%
“…With food being the main culprit in this disease, the differences in dietary habits in different races and regions of the world have influenced the list of common allergens within the particular region or race [17]. For example, the incidence of peanut allergy is not highly prevalent in the Southeast Asia population compared to Western countries, while the incidence of allergy towards cashew nuts was observed to be comparatively higher among children from the Southeast Asia region [18][19][20]. Nonetheless, the main allergens remain largely true to most parts of the world, with eggs, milk, fish, and shellfish being the top four main food allergens, while peanuts, tree nuts, soybeans and wheat are the next four items, thus completing "the big eight" common food allergens [21][22][23].…”
Section: Disease Management and Current Clinical Challengesmentioning
confidence: 99%
“…Inoue et al (2018) reported that cashew nuts are capable of causing severe allergic reaction. There has been an increasing trend of cashew nut allergies in whole world especially Singapore (Chitta et al, 2018). In a study, Van der Valk et al (2014) testified that the prevalence of cashew nut allergy is increasing day by day but the level of evidence for this is low.…”
Section: Accepted Manuscriptmentioning
confidence: 99%